The Use of Video to Enhance the Teaching and Learning Process of Listening English for University Students - Kurniawati, Dewi (English Education: Jurnal Tadris Bahasa Inggris, 2016)
This article discusses and review two journal articles to determine the effect of video in English teaching and learning process especially in listening English, which is always referred to as a boring lesson. As we know that students are always feel trouble before trying Listening lessons. Most of people think that Listening class is always synonymous with listening and mention or filling in the blanks or answer questions then the class should be quiet. So, the teachers must make the class become more interactive. On the Interactive class, students not only listen, filling in the blanks, and answer questions, but they also discuss, dialogue, debate in conversation with each other and teachers can also combine the game in that classroom learning more fun and interactive. Everyone can participate in the class of Listening in the sense that they can improve their skills in listening, grammar, pronunciation, vocabulary, and speaking. Teachers assess Listening through the application of appropriate assessment with learning Listening, such as how well they capture the information they hear from the voice or video then they can discuss it together with each other in the classroom (could play, debates, discussions, etc.).